Blood-brain barrier receptors and transporters: an insight on their function and how to exploit them through nanotechnology. (4th March 2019) - Moura, Rui Pedro; Martins, Cláudia; Pinto, Soraia; Sousa, Flávia; Sarmento, Bruno
ABSTRACT: Introduction : The blood-brain barrier (BBB) is a highly limiting barrier that prevents the brain from contacting with several circulating molecules, including harmful agents. However, certain systemic nutrients and macromolecules are able to cross the BBB and reach the brain parenchyma, involving the interaction with multiple receptors and/or transporters at the BBB surface. Nanotechnology allows the creation of drug vehicles, functionalized with targeting ligands for binding specific BBB receptors and/or transporters, hence triggering the transport through this biobarrier. Areas covered : This review focuses the BBB receptors/transporters to be exploited in regard to their overall structure and biologic function, as well as their role in the development of strategies envisaging drug delivery to the brain. Then, the interplay between the targeting of these BBB receptors/transporters and nanotechnology is explored, as they can increase by several-fold the effectiveness of brain-targeted therapies. Expert opinion : Nanomedicine may be particularly useful in brain drug delivery, mainly due to the possibility of functionalizing nanoparticles to target specific receptors/transporters. Since the BBB is endowed with numerous receptors and transporters responsible for regulating the proper metabolic activity of the brain, their targeting can be a promising bypass strategy to circumvent the hurdle that the BBB represents for brain drug delivery.